An Implementation of Secure Data Exchange in Wireless Delay Tolerant Network Using Attribute-Based Encryption - Sudarsono, Amang; Nakanishi, Toru (2014 Second International Symposium on Computing and Networking, 2014)
Recently, Delay Tolerant Networks (DTNs) have been intensively researched to overcome unstable communication due to the intermittent link connection, delay, and losses in wireless communications. In wireless DTNs, content data are exchanged by storing and forwarding approach to enable continuous connectivity. However, since the participating nodes are not fully trusted, the secure data exchange mechanism in the DTNs would be strongly desirable. In this paper, we propose an implementation of secure data exchange in the wireless DTNs using Attribute-Based Encryption (ABE) to provide two properties: (i) content data can be accessed by only authorized nodes that are dynamically defined by a policy on the attributes, and (ii) routing messages are attribute-based authenticated such that only the attribute-based authorized nodes can exchange the routing messages.